2009
DOI: 10.1007/dcr.0b013e3181b13536
|View full text |Cite
|
Sign up to set email alerts
|

Single-Stage Totally Robotic Dissection for Rectal Cancer Surgery: Technique and Short-Term Outcome in 50 Consecutive Patients

Abstract: Single-stage robotic dissection for rectal cancer surgery is feasible, and its short-term outcome is acceptable. Our technique can be a suitable procedure to maximize the advantages of the da Vinci system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
92
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(109 citation statements)
references
References 18 publications
12
92
0
5
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19] Prior studies have demonstrated that robotic surgery is feasible and safe 7,[11][12][13][14][15][16][17][18]20,21 but may be associated with higher cost and longer operative duration, particularly for rectal resections. 10,25 Given the single-centre reporting bias present in much of the literature, there is a need for research using multi-institutional data.…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Prior studies have demonstrated that robotic surgery is feasible and safe 7,[11][12][13][14][15][16][17][18]20,21 but may be associated with higher cost and longer operative duration, particularly for rectal resections. 10,25 Given the single-centre reporting bias present in much of the literature, there is a need for research using multi-institutional data.…”
mentioning
confidence: 99%
“…nos 52 pacientes submetidos à cirurgia com preservação esfincteriana, apenas um (1,7%) desenvolveu deiscência anastomótica. apesar dos diversos critérios adotados por diferentes autores, nossa taxa de deiscência anastomótica é inferior àquela encontrada na literatura, que varia de 3 até 17% para pacientes submetidos à ETM com preservação esfincteriana por técnica aberta, laparoscópica ou robótica 2,[20][21][22][23][24][25] . De acordo com a recomendação da aJcc, é necessária uma amostra linfonodal de no mínimo 10 a 14 linfonodos para um adequado estudo histopatoló-gico.…”
Section: Discussionunclassified
“…aceita-se um número ainda menor em pacientes submetidos à quimiorradioterapia pré-operatória 26 . em nossa série, apesar de 80% dos pacientes terem sidos submetidos a tratamento neoadjuvante, o núme-ro médio de linfonodos ressecados foi de 18,7. nosso resultado, em termos de amostragem linfonodal, é superior quando comparados aqueles reportados em outras séries de eTM por técnica aberta, laparoscópica ou robótica 2,3,[20][21][22][23][24]27,28 . Diversos estudos não randomizados demonstraram que a eTM com margem radial livre de invasão tumoral reduz a taxa de recidiva local 26 .…”
Section: Discussionunclassified
“…For this laparoscopic procedure, there are alternatives such as hand-assisted ultra-low resection [98] one handsize incision surgery [99] and robot-assisted rectum laparoscopic resection [100][101][102].…”
Section: 7% [Consensus]; Gor A: 857% [Consensus])mentioning
confidence: 99%